Analisis faktor-faktor yang mempengaruhi minat siswa SMK melanjutkan pendidikan ke perguruan tinggi - Novelsa, Fitri; Afdal, Afdal (Universitas Negeri Padang, 2023)
Interest in continuing higher education is a desire that comes from within students, which is accompanied by determination and effort. Interests have a very important role in a person's life and have a big impact on his attitude and behavior. This study aims to determine the factors that influence the interest of SMK students to continue their education to tertiary institutions. This research is a qualitative research with a phenomenological approach. The subjects in this study were 7 people, 3 main subjects namely vocational students who had an interest in continuing their education in tertiary institutions, 4 informants consisting of parents and teachers using the Snowball Sampling technique. The instruments in this study were interview guides, observations , recording equipment and documentation, while the analysis of the data that has been obtained from the results of the interviews, is then used as a transcript, coded, and given a theme as a result of the findings and after that the data is interpreted. The results of the study show that there are two factors that influence the interest of vocational students in continuing their education to tertiary institutions, namely internal and external factors. Internal factors that influence the interest of vocational students to continue their education to tertiary institutions are attention, desire, motivation and needs. While the external factors are encouragement from parents, encouragement from peers, encouragement from teachers, availability of facilities and infrastructure, and environmental conditions.